The Arapaho language - Moss, Alonzo, author; Cowell, Andrew, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2008)
The Arapaho Language is the definitive reference grammar of an endangered Algonquian language. Arapaho differs strikingly from other Algonquian languages, making it particularly relevant to the study of historical linguistics and the evolution of grammar. Andrew Cowell and Alonzo Moss Sr. document Arapaho's interesting features, including a pitch-based accent system with no exact Algonquian parallels, radical innovations in the verb system, and complex contrasts between affirmative and non-affirmative statements. Cowell and Moss detail strategies used by speakers of this highly polysynthetic.
1. The Arapaho People and the Social Contexts of the Arapaho Language -- 2. The Aims and Purposes of this Grammar -- 3. The Arapaho Language Sources Used -- 4. General Introduction to the Structure of the Arapaho Language -- 5. Organization of the Grammar.
Keywords: Arapaho language -- Grammar